PTSL Program in the Context of Conflict Prevention and Land Disputes - Hascaria Budi Prasetyo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
That the status of land ownership in Indonesia is still not completely registered, for example customary landin a few Territories in Indonesia are still not registered, so in order to obtain proof of land ownership, parties who control customary property rights must submit an application for land registrationfirst time through the local land office. Often, in several cases, customary land cannot be registered due to various reasons, such as a lack of information or the unavailability of a fee to register the land. Customary land that has not been registered will result in the vulnerability of land disputes or conflictsin later days, and this is anticipated by establishing a Complete Systematic Land Registration procedure by the Government through the Ministry of Agrarian Affairs and Spatial Planning with the APBN/APBD budget. The purpose of this legal research is nothing elseis as a means of adding knowledge in the field of law which is expected to be of benefit to practitioners and the public. Methods This legal research uses a normative juridical research method which is carried out by examining literature or secondary data using a conceptual, statutory and case approach. The results of this study are that PTSL can be a solution for the Government in completing the programcertification all plots of land that exist on Indonesian soil and can prevent and know which land plots will have the potential for conflict, the benefits of PTSL can also reduce the potential for misconduct by village officials in providing land history documents or proof of physical ownership of customary land. That PTSL has a series of procedures that are passed by involving the village to get maximum results in issuingcertificate which is the spearhead of the PTSL activities. The series of PTSL procedures, namely planning, location determination, preparation, formation and determination of the PTSL adjudication committee and task force, counseling, collection of physical data and collection of juridical data, research on juridical data to prove rights, announcement of physical data and juridical data and their ratification, confirmation of conversion, recognition of rights and grant of rights, bookkeeping of rights, issuance of certificates of land rights, documentation and submission of activity results and reporting.